1997
DOI: 10.2527/1997.753781x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic changes during the transition from the fed to the acute feed-deprived state in prepuberal and mature gilts.

Abstract: The present study compared the metabolic response to acute feed deprivation in ovariectomized prepuberal (P; n = 6), 62 +/- 2 kg BW, and mature (M; n = 6) gilts, 124 +/- 4 kg BW. Blood was collected at 1, 2, 3, 4, 6, 8, 12, 16, 20, 24, 28, 32, 40, and 48 h after initiation of feeding. Samples were quantified for glucose, insulin, free fatty acids (FFA), beta-hydroxybutyrate (HBA), IGF-I, IGF binding proteins (BP)-1 to -4, cortisol, and amino acids (AA). At 24 h, blood samples were collected every 15 min for 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
21
1
3

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 41 publications
(54 reference statements)
6
21
1
3
Order By: Relevance
“…However, the present study failed to show a significant difference in IGFBP levels between restricted and well-fed gilts. This finding was in agreement with the lack of effect of a 48 h food deprivation in prepubertal and mature gilts [1]. This suggests that the sensitivity of plasma IGFBPs to feed restriction differs between pubertal and younger animals.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, the present study failed to show a significant difference in IGFBP levels between restricted and well-fed gilts. This finding was in agreement with the lack of effect of a 48 h food deprivation in prepubertal and mature gilts [1]. This suggests that the sensitivity of plasma IGFBPs to feed restriction differs between pubertal and younger animals.…”
Section: Discussionsupporting
confidence: 81%
“…has also been described by Mao et al [18]. The finding of a lower plasma IGF-I concentration in feed-restricted gilts is consistent with the response to feed deprivation or restriction previously reported in young growing pigs [5,8,9], prepubertal and mature gilts [1,6] and lactating sows [18,27]. Because the liver is considered as one of the major sites of IGF-I production, it has often been indicated that the low concentration of IGF-I results from a decrease in GH binding.…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, several AA share a common AA transporter with large neutral AA (LNAA), and their uptake into the brain depends on the LNAA concentrations [28]. In pigs, brain serotonin concentrations are increased dose-dependently by dietary supplementation of tryptophan to a deficient ration [29], but it is decreased by additional crude protein or additional LNAA [29,30] Barb et al [31] reported that 48-h fasting reduced the tyrosine/LNAA ratio in the plasma of prepuberal gilts. These gilts exhibited an alteration in GH secretion but not in LH secretion.…”
Section: Discussionmentioning
confidence: 99%
“…probably resulted in short-term increases in plasma free fatty acid levels before morning feeding (Barb et al, 1997;Inoue et al, 2005), which in turn can stimulate glucose-stimulated insulin secretion (Haber et al, 2003;Itoh et al, 2003). As insulin responses differ between morning and afternoon feedings, studies investigating effects of insulin on, for example, follicle development should consider both insulin responses.…”
mentioning
confidence: 99%